Catalytic pyrolysis of soda lignin over zeolites using pyrolysis gas chromatography-mass spectrometry. (November 2019) - Kumar, Adarsh; Kumar, Avnish; Kumar, Jitendra; Bhaskar, Thallada
Highlights: Soda lignin, which is underutilised was used for Py-GC/MS studies at different temperatures (500–900 °C) Low cost and commercially available ZSM-5, Mordenite, Y-Zeolite evaluated for pyrolysis. Pore size and acidity of zeolites have significant effect on product distribution. Y-zeolite is best catalytic system for aromatic production from Soda lignin. Abstract: Catalytic fast pyrolysis of soda lignin was examined at different temperatures (500, 600, 700, 800 and 900 °C) in the presence of three zeolites with different Si/Al ratio using the Py–GC/MS in order to investigate best catalytic system. The three zeolites are y-zeolite (8–9), mordenite (15–17), ZSM-5 (30–40), which have static pore sizes 0.74, 0.65, and 0.59 nm respectively. The shape and acidity of zeolites, as well as pyrolysis temperature, have a significant effect on product distribution in catalytic fast pyrolysis. Y-zeolite was the most effective catalytic system among all catalysts for deomethoxylation and dehydroxylation of small oxygenates as well as bulky oxygenates to produce aromatics. However, mordenite and ZSM-5 could not convert the large oxygenates due to size exclusion and pore blockage. Highest yield of aromatics with significant amount of aromatic dimers was obtained over y-zeolite and then yield of aromatics followed in order by mordenite and ZSM-5 at 800 °C.